Perceived organisational support and employees' performance: the mediating role of affective commitment. (17th July 2020) - Yücel, İlhami and Ribeiro, Neuza and Gomes, Daniel Roque
This paper aims to understand if workers' affective commitment (AC) mediates the relationship between perceived organisational support (POS) and individual performance (IP). Using a sample of 476 professionals of a Turkish hospital, structural equation modelling was used to test for the model of analysis. Results revealed that: 1) POS is positively related with employees' AC; 2) POS is positively related with IP; 3) AC is positively related with IP; 4) AC fully mediates the relationship between POS and IP. This study suggests that supporting employees is a valid path for the development of an affective bond with the organisation, which in turn fosters employees' effectiveness.